EFEKTIFITAS WAKTU BELAJAR PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN PADA PESERTA DIDIK SEKOLAH MENENGAH ATAS - Ekan Andiyanto; Victor G. Simanjuntak; Mimi Haetami (Universitas Tanjungpura, 2020)
AbstractTime effectiveness is the most important principle in the learning process, the effectiveness in this writing is the role of students in utilizing / optimizing the physical education learning time. Students who are able to utilize / optimize the learning time of physical education will of course have a satisfactory ability in teaching and learning process and the success of physical education program will be synergized and material education will be fulfilled. The method used in this research included in the type of descriptive research with quantitative approach. Based on the calculation of the percentage of learning time effectiveness in the subjects of PJOK in high school students of the X-Class of South Pontianak sub-district are as follows: SMA Al-Madani, proportion of time utilization (63.33%) with total student involvement (83.33%), SMA Santun Untan, proportion of time utilization (46,67%) with number of student involvement (75,00%), SMA Islamiyah: proportion of time utilization (44,44%), and student involvement (85,00%), SMA Boedi Oetomo, proportion of time utilization (44.44%) with total student involvement (61.90%), SMK Boedi Oetomo, proportion of time utilization (46.67%), and number of student involvement (45.00%).Keywords: Effectiveness, Study, TimeAbstractTime effectiveness is the most important principle in the learning process, the effectiveness in this writing is the role of students in utilizing / optimizing the physical education learning time. Students who are able to utilize / optimize the learning time of physical education will of course have a satisfactory ability in teaching and learning process and the success of physical education program will be synergized and material education will be fulfilled. The method used in this research included in the type of descriptive research with quantitative approach. Based on the calculation of the percentage of learning time effectiveness in the subjects of PJOK in high school students of the X-Class of South Pontianak sub-district are as follows: SMA Al-Madani, proportion of time utilization (63.33%) with total student involvement (83.33%), SMA Santun Untan, proportion of time utilization (46,67%) with number of student involvement (75,00%), SMA Islamiyah: proportion of time utilization (44,44%), and student involvement (85,00%), SMA Boedi Oetomo, proportion of time utilization (44.44%) with total student involvement (61.90%), SMK Boedi Oetomo, proportion of time utilization (46.67%), and number of student involvement (45.00%). Keywords: Effectiveness, Study, Time